Application of Kalman Filter based Neutral Axis tracking for damage detection in composites structures. (15th January 2018) - Soman, Rohan; Majewska, Katarzyna; Mieloszyk, Magdalena; Malinowski, Pawel; Ostachowicz, Wieslaw
Abstract: Structural Health Monitoring (SHM) systems allow early detection of damage which allows maintenance planning and reduces the maintenance cost. The SHM system should be low cost, suitable for continuous monitoring, able to detect small levels of damage, and insensitive to ambient loading, changes in ambient temperature, and measurement noise. Neutral Axis (NA) location is a function of the condition of the structure alone and may be used as a damage sensitive feature. It has been shown that through proper signal processing, NA location is insensitive to measurement noise and ambient temperature changes. This paper aims at validating the use of NA as a damage sensitive feature through experimental study. This paper demonstrates the use of multi-rate Kalman Filter (KF) for accurate estimation of NA under different loading conditions. The methodology was employed on a composite beam instrumented with fiber optic strain sensors. Delamination was introduced in the beam and then progressively increased. The beam was subjected to different loading and temperature conditions for the different damage scenarios. The measured strains were then used for NA tracking. The results show that indeed the NA location may be used as a damage sensitive feature. Some of the loading scenarios were difficult to realise in the laboratory, so these loading scenarios were applied on a validated Finite Element (FE) model of the composite beam. The results indicate that under these dynamic loading scenarios, NA may be used for SHM. Based on the results it can be concluded that KF based NA tracking may be applied to structures for in-service SHM.